2013
DOI: 10.1002/tea.21108
|View full text |Cite
|
Sign up to set email alerts
|

Potential teachers' appropriate and inappropriate application of pedagogical resources in a model‐based physics course: A “knowledge in pieces” perspective on teacher learning

Abstract: We used a “knowledge in pieces” perspective on teacher learning to document undergraduates' pedagogical resources in a model‐based physics course for potential teachers. We defined pedagogical resources as small, discrete ideas about teaching science that are applied appropriately or inappropriately in specific contexts. Neither right nor wrong, all pedagogical resources can be used to build toward a more sophisticated pedagogical stance. We collected three kinds of data across this 11‐week course: videotapes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…The use of a classroom simulator to practice pedagogical skills is grounded in this perspective, and represents a new modality of clinical practice. Harlow and colleagues have described pedagogical resources as "small, discrete ideas about teaching… activated in specific contexts to understand the teaching and learning of science" [42] (pg. 1099).…”
Section: Coding Of Las' Impressions Of the Simulatormentioning
confidence: 99%
“…The use of a classroom simulator to practice pedagogical skills is grounded in this perspective, and represents a new modality of clinical practice. Harlow and colleagues have described pedagogical resources as "small, discrete ideas about teaching… activated in specific contexts to understand the teaching and learning of science" [42] (pg. 1099).…”
Section: Coding Of Las' Impressions Of the Simulatormentioning
confidence: 99%
“…Hammer et al [75] describe the general process by which people relate their current situation to familiar past experiences as framing or resource activation, and several studies have shown that students' engagement and apparent abilities are influenced by the framing they adopt [76][77][78]. Similarly, PD researchers have shown that instructors approach teaching in context-dependent ways [79][80][81][82][83], which lends weight to the idea that the framing that faculty take up within workshop settings plays a role in what they gain from their participation. Although faculty may quietly or vocally contest a workshop leader's instructions, every participant will adopt some framing that influences their thinking during the session, regardless of whether or not the workshop leader guides them towards a particular orientation.…”
Section: Student Experiencesmentioning
confidence: 99%
“…A previously-identified TA belief is that "guiding students is less certain than telling them (the right answer)" because it introduces unnecessary uncertainty into the learning process [12]. Researchers have established that instructors who practice guiding students have less negative attitudes toward instructional reform and increased buy-in to inquirybased learning (IBL) [1].…”
Section: Introductionmentioning
confidence: 99%